PERAN BI’AH LUGHAWIYAH DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ARAB SANTRI PUTRI MAMBAUL ULUM BATA – BATA - Latifatul Mahbubah; Masmunah . (FASAHAH, 2025)
Arabic language learning that focuses solely on linguistic theories can lead to students being passive, having difficulty speaking, and feeling insecure. Creating a language environment (bi'ah lughawiyah) is one solution, as it can be an appropriate medium for developing students' language skills. Bi'ah lughawiyah combines theoretical learning and direct practice of the theories that have been studied. This study aims to describe the role of bi'ah lughawiyah in improving the Arabic language skills of female students at the Mambaul Ulum Bata-bata Pamekasan Islamic boarding school. This research uses a descriptive qualitative approach and uses observation, interviews and documentation in collecting data. The results of the study indicate that the implementation of Bi'ah Lughawiyah at the Mambaul Ulum Bata-Bata Islamic Boarding School has proven to play a significant role in improving students' Arabic language skills, both orally and in writing. This can be seen from the development of students' Arabic language skills during discussions, muhawarah, and speeches/lectures using Arabic. The development of students' Arabic language in the written field can also be seen in the various and consistent publications of the wall magazine. Bi'ah lughawiyah is also very helpful in fostering students' self-confidence and fostering discipline.